2014
DOI: 10.1016/j.bbabio.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Stark fluorescence spectroscopy reveals two emitting sites in the dissipative state of FCP antennas

Abstract: Diatoms are characterized by very efficient photoprotective mechanisms where the excess energy is dissipated as heat in the main antenna system constituted by fucoxanthin-chlorophyll (Chl) protein complexes (FCPs). We performed Stark fluorescence spectroscopy on FCPs in their light-harvesting and energy dissipating states. Our results show that two distinct emitting bands are created upon induction of energy dissipation in FCPa and possibly in FCPb. More specifically one band is characterized by broad red shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
5
26
0
Order By: Relevance
“…For example, formation of hydrogen bonds (39,40) and charge transfer states (41)(42)(43) are generally connected to spectral shifts of at least 10 nm, which are larger than the spectral changes considered in the present study. It is of note that, in a recent 77 K Stark fluorescence study on FCP aggregates, a band near 680 nm was identified, which contributed more strongly to the fluorescence and Stark fluorescence spectra of FCPb than to those of FCPa (43), in agreement with the relative abundance of 680-nm emission in the present study. In the same study, the identified ∼680-nm state exhibited no charge transfer character for the FCPa sample, while for FCPb a weak charge transfer character was attributed to this state, even though a similar 680-nm band resolved for a mixture of FCPa and FCPb complexes showed no evidence of charge transfer.…”
Section: Discussionmentioning
confidence: 51%
“…For example, formation of hydrogen bonds (39,40) and charge transfer states (41)(42)(43) are generally connected to spectral shifts of at least 10 nm, which are larger than the spectral changes considered in the present study. It is of note that, in a recent 77 K Stark fluorescence study on FCP aggregates, a band near 680 nm was identified, which contributed more strongly to the fluorescence and Stark fluorescence spectra of FCPb than to those of FCPa (43), in agreement with the relative abundance of 680-nm emission in the present study. In the same study, the identified ∼680-nm state exhibited no charge transfer character for the FCPa sample, while for FCPb a weak charge transfer character was attributed to this state, even though a similar 680-nm band resolved for a mixture of FCPa and FCPb complexes showed no evidence of charge transfer.…”
Section: Discussionmentioning
confidence: 51%
“…tricornutum only trimers of FCPs exist as basic antenna units. These FCPs have a high capacity for aggregation, bind Dtx and might provide the two different quenching sites, that is, the Q1 and Q2 site, of NPQ (Gundermann & Büchel, ; Miloslavina et al, ; Wahadoszamen et al, ). After the termination of the de‐epoxidation reaction, the aggregation of FCPs and the establishment of quenching sites Q1 and Q2 might be detected as a stable, new arrangement of the thylakoid membrane in the present experiments.…”
Section: Discussionmentioning
confidence: 99%
“…This quenching site would allow the fast dissipation of excess light through inter-complex pigment–pigment interactions, induced by conformational changes within the oligomerized antenna and acting independently from the xanthophyll cycle [ 6 , 105 ]. The quenching could either be determined by chlorophyll–chlorophyll interactions [ 106 ] or by chlorophyll-fucoxanthin interaction, attributing a new photoprotective role to the light-harvesting pigment fucoxanthin [ 6 , 107 ].…”
Section: All- Trans -Neoxanthin In Bryopsidalesmentioning
confidence: 99%